Impacts of sintering temperature on the mechanical properties and gamma ray protection capacity of clay bricks - Aljawhara H. Almuqrin; K.A. Mahmoud; M.I. Sayyed; H. Al-Ghamdi (Nuclear Engineering and Technology, 2024)
The current study aims to develop new clay bricks doped with metallic waste for radiation shielding applications. The aforementioned new bricks were fabricated with various metallic waste concentrations under a pressure rate reaching ≈114 MPa and firing temperature of 1100 °C. The impacts of the metallic waste and the firing temperature on the developed brick samples' physical, radiation shielding, and structural properties were studied. In order to identify the fabricated bricks' mineral content, the X-ray diffraction pattern was used. Additionally, the fabricated bricks' porosity and density were experimentally determined, where the porosity was reduced by 28.03%, while their densities increased by ≈ 10.5% by raising the concentration of metallic waste. The linear attenuation coefficient (LAC) for the developed brick was investigated experimentally using a NaI (Tl) scintillation detector over the 0.033–1.408 MeV energy interval. The measured LAC values were enhanced by increasing the concentrations of metallic waste within the fabricated bricks over the examined energy interval. The fabricated brick's LAC enhancement improves the gamma-ray shielding characteristics. Therefore, the fabricated bricks are a cheap and suitable choice for radiation protection applications.